Evidence for human infection with avian influenza A(H9N2) virus via environmental transmission inside live poultry market in Xiamen, China. Issue 1 (28th October 2022) - Jin, Yifei; Cui, Huan; Jiang, Lina; Zhang, Cheng; Li, Jingjing; Cheng, Hongliang; Chen, Zehui; Zheng, Jing; Zhang, Yidun; Fu, Yingying; Li, Jiaming; Li, Li; et al.
Abstract: H9N2 avian influenza virus (AIV) has become prevalent in the live poultry market (LPM) worldwide, and environmental transmission mode is an important way for AIVs to infect human beings in the LPM. To find evidence of human infection with the influenza A(H9N2) virus via environmental contamination, we evaluated one human isolate and three environmental isolates inside LPMs in Xiamen, China. The phylogeny, transmissibility, and pathogenicity of the four isolates were sorted out systematically. As for the H9N2 virus, which evolved alongside the "Avian‐Environment‐Human" spreading chain in LPMs from the summer of 2019 to the summer of 2020, its overall efficiency of contact and aerosol transmissibility improved, which might contribute to the increasing probability of human infection. This study indicated that environmental exposure might act as an important source of human infection in LPMs.